Percutaneous Autologous Fat Injection Following 2-Layer Flap Lower Blepharoplasty for the Correction of Tear Trough Deformity. Issue 5 (July 2018) - Kim, Jeenam; Shin, Hyojeong; Lee, Myungchul; Shin, Donghyeok; Kim, Soonheum; Jo, Dongin; Kim, Cheolkeun; Kim, Heonjoon; Choi, Hyungon
Abstract : Abstract: Tear trough deformity has been an area that has received much attention in terms of esthetic improvements. Fat transposition has been commonly used for the treatment of tear trough deformity. As some patients have had minimal improvement by that method, we propose the use of fat grafting combined with open blepharoplasty to complement the sunken area, including some of anterior maxilla region, and evaluate and precisely remove the excessive tissue. Lower blepharoplasty was performed by separating the skin and muscle flap. The excessive or laxed tissue was evaluated during the procedure and resected in each flap. Fat grafting was performed after completing a lower blepharoplasty, to ensure accurate placement on the spot where the surgeon originally intended. Overcorrection is not recommended. No serious complications were reported during a period of 10 years. Only 4 patients required a secondary fat injection. Patients who require structural correction of the lower eyelid area (eg, aggressive herniated fat, excessive skin laxity, or bulky orbicularis oculi muscle) and who need complementary material to fill the lower lid area (eg, deep, wide sunken area or relative exophthalmos) are good candidates for blepharoplasty with a fat grafting procedure.